CEST‐2.2 overexpression alters lipid metabolism and extends longevity of mitochondrial mutants. (17th March 2022) - Piazzesi, Antonia; Wang, Yiru; Jackson, Joshua; Wischhof, Lena; Zeisler‐Diehl, Viktoria; Scifo, Enzo; Oganezova, Ina; Hoffmann, Thorben; Gómez Martín, Pablo; Bertan, Fabio; Wrobel, Chester J J; Schroeder, Frank C; et al.
Abstract: Mitochondrial dysfunction can either extend or decrease Caenorhabditis elegans lifespan, depending on whether transcriptionally regulated responses can elicit durable stress adaptation to otherwise detrimental lesions. Here, we test the hypothesis that enhanced metabolic flexibility is sufficient to circumvent bioenergetic abnormalities associated with the phenotypic threshold effect, thereby transforming short‐lived mitochondrial mutants into long‐lived ones. We find that CEST‐2.2, a carboxylesterase mainly localizes in the intestine, may stimulate the survival of mitochondrial deficient animals. We report that genetic manipulation of cest‐2.2 expression has a minor lifespan impact on wild‐type nematodes, whereas its overexpression markedly extends the lifespan of complex I‐deficient gas‐1(fc21) mutants. We profile the transcriptome and lipidome of cest‐2.2 overexpressing animals and show that CEST‐2.2 stimulates lipid metabolism and fatty acid beta‐oxidation, thereby enhancing mitochondrial respiratory capacity through complex II and LET‐721/ETFDH, despite the inherited genetic lesion of complex I. Together, our findings unveil a metabolic pathway that, through the tissue‐specific mobilization of lipid deposits, may influence the longevity of mitochondrial mutant C. elegans . SYNOPSIS: Mitochondrial function influences survival and stress resilience in Caenorhabditis elegans . cest‐2.2 overexpression promotes mobilization of lipid deposits and extends lifespan of complex I deficient mutants. cest‐2.2 is a H3.3‐target gene differentially expressed in long‐ versus short‐lived mitochondrial mutant nematodes. CEST‐2.2 O/E is sufficient to promote lifespan extension of short‐lived, mitochondrial complex I deficient gas‐1(fc21) mutants. CEST‐2.2 O/E stimulates lipid catabolism and fatty acid beta‐oxidation in complex I mutants. CEST‐2.2 O/E enhances mitochondrial respiration of gas‐1 mutants. Abstract : Mitochondrial function influences survival and stress resilience in Caenorhabditis elegans . cest‐2.2 overexpression promotes mobilization of lipid deposits and extends lifespan of complex I deficient mutants.